The Influence of Products and Prices on Customer Loyality At the Sharia People's Economic Bank Bakti Makmur Indah Main Branch Office in Sidoarjo - Abdul Majid Toyyibi; Muhammad Adi Satria (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Sharia People's Economic Bank Bakti Makmur Indah Main Branch Office Throughout is one of the sharia banks that has great potential in developing an economy based on Islamic values. This research aims to determine the effect of product and price oncustomer loyality at BPRS Bakti Makmur Indah Main Branch Office Throughout. The object of this research is the BPRS Bakti Makmur Indah Main Branch Office along with quantitative methods using multiple regression test techniques. The respondents in this research were 76 customers. The analytical method used is descriptive analysis, F test and T test with product (X1), price (X2), and customer loyalty (AND). The results of this research show that product and price have a positive and significant effect on customer loyalty. This is proven by the statistical results of the simultaneous f test for the product variable, the calculated f value > f table (31.473>3.12) so that there is a positive and significant influence between the product and price variables simultaneously on customer loyalty or the hypothesis is supported.